2018
DOI: 10.1155/2018/9285164
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Families That Are Positively Deviant for Childhood Obesity in a Latino Population: A Case-Control Study

Abstract: Background Childhood obesity is a complex public health challenge that requires innovative, sustainable solutions. Positive deviance, inspired by the science of complexity, is an approach that examines what allows certain individuals to succeed despite being predicted to fail. This study is aimed at identifying and defining positive deviants for early childhood obesity. Methods This case-control study used medical record data to identify Latino children aged 2–5 and classify them using their longitudinal weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Specifically, a positive deviance approach identifies “social deviants” who have healthy outcomes despite facing the same challenges and having no more resources than their peers [ 104 ]. A social deviance approach to childhood obesity is starting to become more common [ 105 , 106 ]. This work has found self-efficacy to be a salient characteristic of positive deviant families who were able to reduce child adiposity [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a positive deviance approach identifies “social deviants” who have healthy outcomes despite facing the same challenges and having no more resources than their peers [ 104 ]. A social deviance approach to childhood obesity is starting to become more common [ 105 , 106 ]. This work has found self-efficacy to be a salient characteristic of positive deviant families who were able to reduce child adiposity [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental curriculum available in both English and Spanish was developed on the basis of findings from a positive deviance study that identified behaviors and practices from Latino families who were successful in changing their child’s weight status from obese toward a healthy weight [17]. After these behaviors were identified, we used a behavioral intervention mapping approach to create the curriculum for parent mentors to apply with parents in the experimental (positive deviance) arm [22, 23].…”
Section: Methodsmentioning
confidence: 99%
“…Identifying the successful behaviors of positive deviants can inform an intervention for the larger population at risk. We previously identified core characteristics of positive deviants for early childhood obesity in a low-income, Latino population [17]. The potential benefit of using positive deviance is that by identifying strategies that already exist in the community, the intervention may be more scalable and overcome challenges related to cultural beliefs [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, our findings on the specific factors associated with positive deviance contrast with those of other recent studies of low-income, predominantly Hispanic communities. Foster et al conducted a similar study in San Antonio, Texas, and identified low parental education, high parental self-efficacy, and predominant Mexican cultural identity (low acculturation) among parents, as factors associated with positive deviance for healthy weight trajectories in children aged 2–5 years of age (37). None of these factors were found to be associated with decreasing BMI in our study.…”
Section: Discussionmentioning
confidence: 99%